Low-Dose 3-Factor Prothrombin Complex Concentrate for Warfarin Reversal Prior to Heart Transplant. (August 2015) - Kantorovich, Alexander; Fink, Jodie M.; Militello, Michael A.; Wanek, Matthew R.; Smedira, Nicholas G.; Soltesz, Edward G.; Moazami, Nader
Background: Anticoagulation with warfarin is common in patients presenting for heart transplant. Prior to surgery, anticoagulation reversal is necessary to avoid significant intraoperative and perioperative bleeding complications. Commonly, warfarin reversal is achieved with vitamin K and fresh frozen plasma (FFP); however, these therapies have significant limitations. An alternative to FFP for reversal exists with prothrombin complex concentrate (PCC). A warfarin reversal protocol prior to heart transplant was implemented using low-dose PCC at our institution.Objective: To assess blood product use, effectiveness, and safety post–low-dose PCC administration in patients needing warfarin reversal prior to heart transplant compared with historical controls.Methods: This was a single-center, retrospective cohort study. The PCC cohort included patients undergoing heart transplant presenting with an international normalized ratio ≥1.5 on warfarin therapy and who received at least 1 dose of PCC. Blood product use was measured from postoperative day 0 to 2.Results: The PCC and historical control cohorts included 16 and 50 patients, respectively. There was a significant reduction in the use of FFP (4 vs 8 units, P = 0.0239) in the PCC cohort compared with the historical control cohort. No differences were identified in the use of other blood products as well as other secondary efficacy or safety end points.Conclusions: Use of PCC, per the reversal protocol, prior to heart transplant reduced FFP use and showed a non–statistically significant trend toward reductions in the use of other blood products in the intraoperative and perioperative setting, with no difference identified in thrombotic or embolic complications compared with historical controls.